2003
DOI: 10.1021/jp030279g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Incineration of Organic Pollutants on Boron-Doped Diamond Electrode. Evidence for Direct Electrochemical Oxidation Pathway

Abstract: The electrochemical incineration of organic pollutants on a boron-doped diamond (BDD) thin film electrode was examined by bulk electrolysis, and the mechanism of oxidation was investigated. A comparative study with other electrodes such as Pt and glassy carbon (GC) electrodes revealed the superiority of the BDD over these electrodes. The extent of degradation of phenol and formate due to direct oxidation and hydroxyl radicalmediated oxidation were quantified by amperometric measurements. The extent of direct o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
110
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 25 publications
4
110
0
3
Order By: Relevance
“…Although various treatment strategies exist to treat phenols, electrochemistry is a promising new treatment method that numerous researchers have studied with various types of electrodes. Work has been done with titanium [5,6], platinum [7], glassy carbon [8], graphite [9], and boron-doped diamond (BDD) [10,11]. Interest in BDD electrochemistry has increased since the discovery that BDD has several advantages over other types of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Although various treatment strategies exist to treat phenols, electrochemistry is a promising new treatment method that numerous researchers have studied with various types of electrodes. Work has been done with titanium [5,6], platinum [7], glassy carbon [8], graphite [9], and boron-doped diamond (BDD) [10,11]. Interest in BDD electrochemistry has increased since the discovery that BDD has several advantages over other types of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The phenol derivates are toxic and non-biodegradable organic compounds included in the list of priority phenols, which are used/produced in several industrial processes, being commonly used as preservatives, disinfectants, in pulp processing, in the manufacture of pesticides and intermediars [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In the electrochemical processes, the aim is the complete oxidation of organics to CO2 or the conversion of the toxic organics to biocompatible compounds [1]. It has been reported [2,3] that the phenol electrooxidation produces electrode fouling by electropolimerization that leads to a low rate of oxidation, low permeability and strong adhesion on the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Soc. compounds, particularly for the wastewater treatment. [10][11][12][13] In addition, modifications of the BDD surface have been employed for a number of specific applications. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Thus, Duo et al 14 have studied the deposition of small quantities of IrO 2 clusters on the BDD surface by a thermal decomposition technique and observed that the oxygen evolution reaction (OER) was dramatically enhanced with the surface modification.…”
Section: Introductionmentioning
confidence: 99%